Role of parental occupational status and education in the educational attainment of their children - Butt, Muhammad (My University, 2025)
This study investigates the influence of parental occupation, education, their independent and combined effects in outcome of children’s educational attainment in Finland. The study utilizes data from the European Social Survey (ESS) rounds 8, 9, 10, and 11, collected in 2016, 2018, 2020, and 2023 respectively. The sample consists of 3143 respondents aged 30 70 years. The analysis employs a binary logistic regression model which includes the interaction of parental characteristics to find out its effect on children’s education. Furthermore, the study explains its results with predicted probabilities for better understanding of readers. We found that parental education and occupation have positive effects on the educa tion of their offsprings. When we look at their independent effect, parental education is the strongest predictor following parental occupation. We also found that advantage in one parental characteristic compensates for disadvantage in another.
Keywords: parental education, parental occupation, children’s education, compensatory advantage